Teknologi Dalam Penerbitan Ilmiah Pada CV. Doki Course and Training: Studi Role Playing Pada Mahasiswa Prodi Bahasa dan Sastra Arab - Isnaini Rahmawati; Anisyah; Chely Amalia Putri; Iredho Fani Reza; Magfiroh (CV. Doki Course and Training, 2024)
This community service is to find out how to utilize technology in scientific publishing at the CV. Doki Course and Training institution. This community service activity is part of the implementation of Field Experience Practice carried out by Arabic Language and Literature Study Program Students, Faculty of Adab and Humanities, Raden Fatah State Islamic University, Palembang. The method used in community service activities uses role playing. The implementation process of this PPL is arranged based on the Work Program that already exists at CV. Doki Course and Training, namely the Scientific Publishing segment which includes the publication of Proceedings, Books and Journals. This program was implemented on August 1-31, 2024. The results of this program concluded that the use of technology in scientific publishing is a must in the current modern era. CV. Doki Course and Training as a publication institution has succeeded in utilizing sophisticated technology to publish scientific publications in the form of proceedings, periodic journal books. The emphasis on aspects of governance management and publication management is the key to the success of managing technology in scientific publishing.